Confined LiBH4–LiAlH4 in nanopores of activated carbon nanofibers. (15th June 2015) - Plerdsranoy, Praphadsorn; Utke, Rapee
Abstract: Polyacrylonitrile (PAN)-based polymer fiber prepared from electrospinning technique is carbonized and activated (with concentrated KOH solution) to obtain activated carbon nanofiber (ACNF). ACNF is used in this work as a host material for nanocofinement of LiBH4 –LiAlH4 composite via solution impregnation. Successful nanoconfinement and homogeneous distribution of hydride composite on ACNF are confirmed by N2 adsorption-desorption and SEM-EDS-mapping techniques, respectively. Nanoconfined LiBH4 –LiAlH4 in ACNF performs almost single-step decomposition whereas that of milled sample is clearly two-step reaction. Onset dehydrogenation temperature of LiAlH4 from nanoconfined and milled samples is comparable at 100 °C, while that of LiBH4 obtained from nanoconfined sample is up to 80 °C lower than that of milled sample. In addition, significant reduction in main dehydrogenation temperature, especially of LiBH4 in nanoconfined LiBH4 –LiAlH4 as compared with milled LiBH4 –LiAlH4 (Δ T  = up to 94 °C) and with pristine LiBH4 (Δ T  = up to 149 °C) is achieved. Hydrogen contents released and reproduced in the 1st and 2nd dehydrogenations of nanoconfined LiBH4 –LiAlH4 are 30 and 63% superior to those of milled sample. Reversibility of LiBH4, LiAlH4, and/or Li3 AlH6 was accomplished from nanoconfined LiBH4 –LiAlH4 under mild temperature and pressure condition ( T  = 320 °C and P (H2 ) = 80 bar) as compared with other LiBH4 –LiAlH4 (or Al) systems. Highlights: First time nanoconfinement of LiBH4 –LiAlH4 in activated carbon nanofiber. Lower onset and main decomposition temperatures (Δ T  = 80 and 94 °C, respectively). Up to 9.10 and 7.59 wt.% H2 released and reproduced (1st and 2nd cycles, respectively). Milder rehydrogenation condition ( T  = 320 °C, P (H2 ) = 80 bar). Successful reversibility of LiBH4, LiALH4, and/or Li3 AlH6 .